Lower Succinyl-CoA:3-ketoacid-CoA Transferase (SCOT) and ATP Citrate Lyase In Pancreatic Islets of A Rat Model of Type 2 Diabetes: Knockdown of SCOT Inhibits Insulin Release In Rat Insulinoma Cells - Hasan, Noaman M. (2010)
Succinyl-CoA:3-ketoacid-CoA transferase (SCOT) is a mitochondrial enzyme that catalyzes the reversible transfer of coenzyme-A from acetoacetyl-CoA to succinate to form acetoacetate and succinyl-CoA. mRNAs of SCOT and ATP citrate lyase were decreased 55% and 58% and enzyme activities were decreased >70% in pancreatic islets of the GK rat, a model of type 2 diabetes. INS-1 832/13 cells were transfected with shRNAs targeting SCOT mRNA to generate cell lines with reduced SCOT activity. Two cell lines with > 70% knockdown of SCOT activity showed > 70% reduction in glucose- or methyl succinate-plus-β-hydroxybutyrate-stimulated insulin release. Less inhibition of insulin release was observed with two cell lines with less knockdown of SCOT. Previous studies showed knockdown of ATP citrate lyase in INS-1 832/13 cells does not lower insulin release. The results further support work which suggests mitochondrial pathways involving SCOT that supply acetoacetate for export to the cytosol are important for insulin secretion.